LEO STRAUSS’S CRITIC OF MODERN NATURAL RIGHT CONCEPTS AND ITS CONTEMPORARY RELEVANCE - Gajic, Aleksandar (Srpska politička misao, 2026)
This paper reviews Leo Strauss’s critique of modern natural right concepts and their contemporary relevance in the light of the crisis of modernity. The first part of the paper observes Strauss’s interpretative approach to classical political thought, whose main purpose was to rediscover classical wisdom for solving many theoretical and practical contemporary issues. Natural Right and History, Leo Strauss’s best-known work, deals with the topic of the relevance of the idea of natural right in light of the 20th century’s main dilemma of political philosophy – the crisis of modern political and normative order. Therefore, the second part of the paper gives a brief insight into Strauss’s view on the crisis of modernity that is displayed in his work The Three Waves of Modernity. Then the work turns its focus on the field of natural right, where, in the third section of the paper, the opposition between classical and modern natural right concepts is analyzed. The final chapter gives some conclusions on the contemporary relevance of Strauss’s ideas on natural right and its consequences on both contemporary political philosophy and political life. It shows that some of Strauss’s ideas on natural right are more relevant than ever, while others turned out to be problematic, unsuitable, or quite naïve and irrelevant.
Keywords: Leo Strauss; classical natural right; modern natural right; crisis of modernity; virtue; nature; history